Susceptibility-Weighted MR Imaging: A Better Technique in the Detection of Capillary Telangiectasia Compared with T2* Gradient-Echo - Chaudhry, U.S.; De Bruin, D.E.; Policeni, B.A. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Enhancing lesions on brain MR imaging can present a diagnostic quandary as both benign lesions such as brain capillary telangiectasia and pathologic lesions such as demyelination may appear similar. Stagnation of blood in low-flow venous channels of brain capillary telangiectasias results in susceptibility effect secondary to the increased local deoxyhemoglobin. Both T2* gradient-echo imaging and SWI were demonstrated as valuable in the diagnosis of brain capillary telangiectasia. Because SWI is more sensitive to susceptibility changes than gradient-echo, we aim to demonstrate increased diagnostic value of SWI compared with gradient-echo in making the diagnosis of brain capillary telangiectasia. MATERIALS AND METHODS: We retrospectively reviewed the MR images of 17 patients with a presumed diagnosis of brain capillary telangiectasia and who were examined from June 2010 to September 2012. All patients underwent MR imaging at 1.5T with T1, T2, FLAIR, gradient-echo, SWI, and gadolinium-enhanced T1 sequences. Lesions were evaluated for the presence or absence of signal abnormality on each particular sequence. RESULTS: All 17 brain capillary telangiectasias demonstrated distinct signal-intensity loss on SWI compared with 7 of 17 (41%) who showed signal-intensity loss on gradient-echo. The increased frequency of detection using SWI versus gradient-echo is statistically significant (z = 2.85, P < .01; χ2 = 8.10, P < .01). Six of the lesions showed signal-intensity changes on T1 and/or T2 whereas the remaining lesions were isointense to normal brain. CONCLUSIONS: Brain capillary telangiectasias are more conspicuous on SWI than gradient-echo imaging and other precontrast MR imaging. SWI is a valuable tool in diagnosing these benign lesions and should serve to increase diagnostic confidence. BCTbrain capillary telangiectasiaGREgradient-echo